Solution-focused brief therapy for common mental disorders in the light of empirically supported treatment revised criteria: a systematic review protocol - Pękala, Krzysztof; Seweryn, Michał; Żak, Andreea M. (Frontiers in Psychiatry, 2025)
BackgroundSolution-Focused Brief Therapy (SFBT) is a short-term, goal-directed therapeutic approach widely used across diverse settings. While prior evidence supports its overall effectiveness, the empirical status of SFBT as a treatment for common mental disorders (CMD) remains unclear. This protocol outlines a systematic review aiming to evaluate the efficacy, effectiveness, mechanisms of change, and cost-effectiveness of SFBT in the treatment of CMD following the updated empirically supported treatment criteria.MethodsA systematic search for recently published systematic reviews, randomized controlled trials, and high-quality non-randomized studies of intervention examining SFBT in adults (≥18 years) diagnosed with CMDs will be performed. Risk of bias and methodological quality will be assessed. Data selection, extraction, and rating will be conducted independently by at least two reviewers.OutcomesPrimary outcomes include symptom reduction in CMD; secondary outcomes encompass, among other improvements in psychosocial functioning and remission rates. Additional outcomes involve cost-effectiveness, adverse effects, and evidence for mechanisms of change. Meta-analysis and narrative synthesis will be performed when appropriate.Expected ImpactThe rigorous assessment of SFBT empirical status in the context of CMD can potentially influence recommendations for clinical practice, guideline development, and future research.